The relationship of service quality towards customer loyalty at Melaka International Trade Centre (MITC) / Muhamad Zaki Ibrahim - Ibrahim, Muhamad Zaki (Faculty of Business and Management, 2007)
This chapter will provide the overview of the research, which title "The Relationship of Service Quality towards Customer Loyalty at Melaka International Trade Centre (MITC)". The main objective of this research is to study in depth and measuring the level of customer loyalty towards Melaka International Trade Centre (MITC) by using service quality as the instrument. In addition, it is to support that using service quality is suitable and effective in evaluate the customer loyalty level in the service company especially in Meetings, Incentives, Conventions, and Exhibitions (MICE) centre.